Medical decisions in organ donors and heart transplant candidates with history of COVID‐19 infection: An international practice survey. Issue 7 (8th June 2022) - Sadeh, Ben; Ugolini, Sharon; Pinzon, Omar Wever; Potapov, Evgenij V.; Selzman, Craig H.; Bader, Feras; Zuckermann, Andreas o; Gomez‐Mesa, Juan Esteban; Shah, Kevin S.; Alharethi, Rami; Morejon‐Barragan, Paola; Hanff, Thomas; et al.
Abstract: Background: A growing proportion of transplant donors and recipients have a history of COVID‐19 infection. This study sought to characterize clinical practice after recipient or donor COVID‐19 infection. Methods: An online survey was distributed to heart transplant clinicians through a professional society message board and social media. Responses were collected between September 29 and November 5, 2021. Results: There were 222 health care professionals (68% transplant cardiologists, 22% transplant surgeons, 10% other) across diverse geographic regions who completed the survey. While there was significant variation in donor acceptance, as it relates to past and current COVID‐19 infection, the respondents were fairly cautious: 28% would not typically accept a donor with a history of COVID‐19 regardless of the infection course and > 80% would not accept donors who had evidence of myocardial dysfunction during past COVID‐19 infection, or who died of COVID‐19 or its complications. The timing of candidate reactivation on the waiting list after COVID‐19 infection also varied and often diverged from scenarios addressed by social guidelines. Eighty‐one percent of the respondents felt COVID‐19 vaccine should be mandatory before transplant, but this rate varied by geographic region. Conclusion: Our results reflect evolving experience of the heart transplant field at a time of lack of high‐quality evidence. In the absence of longer‐term outcome data for donors and transplant candidates with history of COVID‐19 infection, clinicians remain cautious; however, this approach will likely need to be refined as an increasing proportion of the population will continue to be infected with COVID‐19.